The partnership as a factor of sustainable growth for the companies in the information technology sector in Brazil - Albuquerque, D. C. (2014)
In the last decade, some companies in the field of information technology had been significant growth while others have not reached the same results. We also observed that some of these companies began to adopt strategies with a focus on partnership. There are a number of questions about the partnership as a factor of sustainable growth for the companies in the information technology Sector. This article presents some concepts and interpretations based on literature review, expert opinion, field research via questionnaires and the own professional experience.